Analysis of the Use of Environmentally Friendly Building Materials and Construction Waste Management on Cost Efficiency and Project Sustainability in Karawang - Joni Kutu' Kampilong; Weda Febriyanto; Yudhi Juliardiyanto Nugroho; Ramdan Yusuf (Westscience Press, 2024)
This study investigates the impact of environmentally friendly building materials and construction waste management on cost efficiency and project sustainability in Karawang. A quantitative analysis was conducted using a sample of 150 respondents from the construction sector, with data collected through a structured survey based on a Likert scale of 1 to 5. Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) was employed to analyze the relationships between the variables. The results show that both environmentally friendly materials and construction waste management significantly improve cost efficiency and project sustainability. Construction waste management exhibited a stronger influence on both outcomes, emphasizing its importance in reducing costs and promoting environmental responsibility. The findings suggest that adopting sustainable construction practices can enhance financial performance while contributing to long-term sustainability, offering valuable insights for construction companies and policymakers.